Cabozantinib-Associated Exudative Retinal Detachment and Choroiditis: A Case Report - Kirk A.J. Stephenson; Bryon R. McKay; Katherine E. Paton (Journal of Current Ophthalmology)
Purpose To describe the first reported instance of an acute chorioretinal inflammatory response to cabozantinib. Methods Case report. Results A 54-year-old Asian male presented with blurred vision 2 weeks following the commencement of cabozantinib for metastatic renal cell carcinoma. Ophthalmic examination revealed bilateral exudative retinal detachments and choroiditis in a pattern similar to Vogt–Koyanagi–Harada disease. Further investigations revealed latent tuberculosis (TB), and management of this ocular adverse event was with cabozantinib cessation, high-dose oral prednisone, single-agent anti-TB therapy, and methotrexate. Return of visual function and ocular anatomy occurred within 1 month. Conclusions Modern pharmacotherapy for metastatic cancer may increase survival, but a range of ocular and systemic adverse events are frequently seen. Screening and early intervention can mitigate adverse events and treatment burden, while maximizing benefits for this disadvantaged patient group.